An Improvement of Exertional Dyspnea by the Reintroduction of Anti-EGFR Antibody in Patients with Metastatic Rectal Cancer Who Developed Cancerous Lymphangiopathy: A Case Report - Masatsune Shibutani; Hideki Tanda; Tatsunari Fukuoka; Hiroaki Kasashima; Shinichiro Kashiwagi; Kiyoshi Maeda (Case Reports in Oncology, 2024)
Introduction: Reexposure to anti-EGFR antibodies, such as a reintroduction or rechallenge with anti-EGFR antibodies, has attracted much attention in the field of metastatic colorectal cancer. A reintroduction of anti-EGFR antibodies often shows good therapeutic outcomes, as most patients eligible for such reintroduction discontinued treatment due to adverse events despite a good treatment response during front-line treatment. We herein report a case demonstrating an improvement in exertional dyspnea after the reintroduction of anti-EGFR antibody in a patient with metastatic rectal cancer who developed cancerous lymphangiopathy. Case Presentation: A 68-year-old man who had undergone curative surgery for stage IIIB rectal cancer was diagnosed with multiple lung metastases. During the late-line treatment, respiratory failure developed because of multiple lung metastases and cancerous lymphangiopathy. Two months after the initiation of irinotecan + cetuximab, which had been discontinued due to acneiform eruptions despite a good treatment response as a first-line treatment, his dyspnea and performance status dramatically improved. Conclusion: This case indicates that the reintroduction of anti-EGFR antibody to patients who have discontinued anti-EGFR antibody due to skin toxicity despite a good treatment response is a very useful treatment option for metastatic colorectal cancer.